Adsorption of branched polymer chains onto solid substrates - Özer, Sümeyye. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Polymer thin films have a wide range of applications in photovoltaic materials, biomedical coatings, and nanolithography. Thin films are prepared using either solution or melt deposition techniques in which residual stresses are formed during the deposition. Annealing process above glass transition temperature (Tg) of polymers to remove the residual solvent whereas some of the polymer chains to adsorb onto the surface. Presence of adsorbed polymer layer in thin films cause deviations from bulk behavior in physical properties. In earlier studies, segment-substrate interactions are varied to manipulate the enthalpic effect which in general favors adsorption. When each segment pins to the substrate, polymer chains lose conformational entropy which works against adsorption. In this study, we have elucidated the role of entropic effect by varying the polymer architecture on the structure and growth kinetics of adsorbed layer by ellipsometry, X-ray reflectivity, and atomic force microscopy. Linear polystyrene (PS), 4-arm star PS, comb PS, and centipede PS of similar total molecular weight are used on hydrophilic SiOx and hydrophobic SiH to determine the effect of architecture on adsorption. Quality of the leaching solvent is also investigated for short and long leaching times. Our results demonstrate that the normalized layer thickness increases as the branching increases. Centipede PS always adsorb to give the thickest layers, whereas linear PS forms the thinnest adsorbed layers. For all the polymers since the enthalpic interactions are the same, the difference is the result of a reduction in the entropic loss for more branched architectures. All polymers yield thicker adsorbed layers on SiH surfaces than on SiOx surfaces due to stronger segment-substrate interactions. Toluene is found to be a better solvent for leaching than chloroform despite the opposite claims in the literature. For the first time, we have shown that just modifying the entropic contribution through polymer architecture opens up a new path to control the formation of adsorbed polymer layers.
Keywords: Polymers.